EFFECT OF WORK ENVIRONMENT AND OCCUPATIONAL HEALTH SAFETY ON EMPLOYEE PERFORMANCE AT PT. SCHNEIDER ELECTRIC BATAM: English - Meta Hariska Tanjung; Nora Pitri Nainggolan (Universitas Putera Batam, 2022)
The purpose of this research is to ascertain the following: (1) the influence of the work environment on employee performance; (2) the effect of occupational health safety on employee performance; and (3) the effect of the work environment and employee health safety on employee performance.This is a quantitative study using the survey approach.The population in this research was 300, with a total of 171 samples gathered using the Slovin formula computation. Proportionate Stratified Sample is the sampling method employed.Multiple Linear Regression is used to analyze the data. The findings of this research reveal that the work environment has a little influence on the performance of PT Schneider Electric Batam personnel.Occupational health and safety have a marginal influence on the performance of PT Schneider Electric Batam personnel.Simultaneously, the work environment and occupational health and safety have a substantial impact on the performance of PT Schneider Electric Batam personnel.